2015
DOI: 10.1097/ccm.0000000000001164
|View full text |Cite
|
Sign up to set email alerts
|

Community-, Healthcare-, and Hospital-Acquired Severe Sepsis Hospitalizations in the University HealthSystem Consortium

Abstract: Objectives Severe sepsis poses a major burden on the U.S. healthcare system. Previous epidemiologic studies have not differentiated community-acquired severe sepsis from healthcare-associated severe sepsis or hospital-acquired severe sepsis hospitalizations. We sought to compare and contrast community-acquired severe sepsis, healthcare-associated severe sepsis, and hospital-acquired severe sepsis hospitalizations in a national hospital sample. Setting United States Interventions None Measurements & Main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
124
2
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(139 citation statements)
references
References 22 publications
7
124
2
6
Order By: Relevance
“…Thus, the mortality can be higher with the updated third definition. In our study, we used the definition proposed by Angus  et al ,10 which was subsequently used in identifying patients with sepsis from EHR 12. Patients identified in this way were generally consistent with the third sepsis definition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the mortality can be higher with the updated third definition. In our study, we used the definition proposed by Angus  et al ,10 which was subsequently used in identifying patients with sepsis from EHR 12. Patients identified in this way were generally consistent with the third sepsis definition.…”
Section: Discussionmentioning
confidence: 99%
“…Sepsis was defined as a diagnosis of infection plus acute organ dysfunction 10 11. The definition was proposed by Angus  et al ,10 and was subsequently used in identifying patients with sepsis from electronic health record (EHR) 12…”
Section: Methodsmentioning
confidence: 99%
“…This was based on a meta-analysis of the literature and a large cohort study of sepsis patients, demonstrating the prognostic value of lactate >2 mmol/L for mortality in sepsis [14]. CAP is regarded a major source of sepsis [33]; accordingly, recommendations of adequate sepsis management have been incorporated within recent CAP guidelines [9] and implemented within CAP management bundles [26]. One study evaluating the effect of sepsis bundle implementation in CAP patients revealed that lactate measurement was independently associated with lower mortality [27].…”
Section: Discussionmentioning
confidence: 99%
“…Because of our focus on “community-acquired” rather than “hospital-acquired” sepsis, we did not utilize clinical data from later points of hospitalization. (16)…”
Section: Methodsmentioning
confidence: 99%
“…We are currently linking REGARDS participants to their corresponding Medicare claims, which may allow identification of hospital-acquired or healthcare-associated sepsis. (16)…”
Section: Limitationsmentioning
confidence: 99%